The Effect of Endorphin Massage on the Adaptation of Labor Pain in the Active Phase I of Inpartu Mothers at Polindes Larasati (Sekardadi Village, Jenu District, Tuban Regency) - Dyah Pitaloka; Tiara Putri Ryandini (Aloha International Journal of Health Advancement (AIJHA), 2020)
The process of childbirth is identical to the onset of pain. The most dominant pain is felt especially in the active phase of the first stage of labor. The 1st stage of labor is the beginning of labor contractions characterized by progressive cervical changes ending with complete dilatation (10 cm). One of the problems that occur in first stage labor pain is caused by uterine contractions that cause cervical dilation and thinning. Through endorphine massage, which is a touch technique or light massage given to pregnant women before delivery that can normalize heart rate, blood pressure, and can increase the relaxed condition in the body of pregnant women by triggering a feeling of comfort through the skin surface so that by doing the massage for 20 minutes, then the pain in labor will be reduced. This study uses a quantitative research method with a static group comparison design. Measurements were made in the treatment group that was given an endorphine massage for 20 minutes in the active phase. The population in this study were all inpartu mothers who gave birth at Polindes Larasati. This research was conducted in Sekardadi Village, Jenu District, Tuban Regency. The sample in this study were some of the pregnant women who met the inclusion criteria as many as 14 respondents. McNemar statistical test results obtained p value = 0.031 (α < 0.05), thus there is an effect of endorphine massage on the adaptation of labor pain in the active phase of the first stage of inpartum mothers. From the results of the study, it was concluded that there was an effect of endorphine massage on pain adaptation because endorphine massage can stimulate the body to release endorphins which are pain relievers. It is hoped that health workers can provide health education about endorphine massage to the community so that later it is hoped that all people will be able to apply endorphine massage to overcome pain in labor. Keywords: endorphine massage; pain adaptation